1991
DOI: 10.1093/brain/114.2.1013
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Multiple Sclerosis Lesions Detected by Magnetic Resonance Imaging in Unfixed Postmortem Central Nervous System Tissue

Abstract: Postmortem unfixed whole brains from 17 multiple sclerosis and 6 control cases were examined by magnetic resonance imaging (MRI) using a T2-weighted spin echo sequence and histology to determine the relationship between areas of abnormal MRI signal and underlying pathological change. In group 1, small MRI lesions and correspondingly small plaques, most of which were chronic, were detected histologically in 5 brains. In 4 brains there were more extensive areas of both abnormal signal and histological plaques wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
7

Year Published

1992
1992
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(92 citation statements)
references
References 0 publications
3
82
0
7
Order By: Relevance
“…The pathology of MS is usually thought of as being confined to the white matter, but the observation that autoantibodies to neurofilaments were seen in MS patients and not controls indicates that gray matter of the brain may also be involved in the disease. This confirms previous observations indicating the presence of gray matter pathology in MS patients using magnetic resonance imaging (12) and studies demonstrating the presence of antibodies to the 69-kDa neurofilament protein (11).…”
Section: Discussionsupporting
confidence: 92%
“…The pathology of MS is usually thought of as being confined to the white matter, but the observation that autoantibodies to neurofilaments were seen in MS patients and not controls indicates that gray matter of the brain may also be involved in the disease. This confirms previous observations indicating the presence of gray matter pathology in MS patients using magnetic resonance imaging (12) and studies demonstrating the presence of antibodies to the 69-kDa neurofilament protein (11).…”
Section: Discussionsupporting
confidence: 92%
“…Several dedicated pulse sequences have been designed to disentangle the complex contrast mechanisms, in order to highlight one speci¢c physical property. In doing so, one can obtain information about the physical properties 1676 F. Barkhof and M. vanWalderveen (Newcombe et al 1991;Stewart et al 1984;Van Waesberghe et al 1999;Barkhof et al 1993). The typical sclerotic lesions that are found macroscopically at post-mortem are displayed as clearly demarcated lesions with a very high signal.…”
Section: Conventional Nmr Imaging: a Mixture Of Physical Parametersmentioning
confidence: 99%
“…However, both the pathologic (17,18) and imaging studies (19,20) have shown that lesions could involve gray matter, although sparsely. Recent study indicates that neuronal axons may be damaged in acute and chronic lesions, suggesting that gray matter (neuronal cell bodies) may ultimately suffer damage (21).…”
mentioning
confidence: 99%